Bureaucracy, Instructions, and Paperwork – The Gathering of Data about the Three Kingdoms of Nature in the Americas, 1770-1815 - Irina Podgorny (Centre de Recherches sur les Mondes Américains, 2019)
This paper examines the system of production and circulation of knowledge linked to Spanish bureaucracy and the Atlantic trade. Based on primary sources from the General Archive of the Indies (AGI), the General Archive of the Nation (Argentina-AGN), the Archive of the Royal College of Surgeons (London-RCS), and on secondary bibliography, this article, rather than focus on the objects collected, considers the documents that resulted from the “necessity” of collecting minerals, plants and animals, revealing the true protagonists of this story: the pathways of bureaucracy and the flow of paperwork where data about nature and man in the Americas were generated and took shape. At the same time, it reflects on the adoption of the "three kingdoms of nature" defined by Linnaeus and adopted in the instructions to complete the Royal Cabinet of Natural History of Madrid.